1986
DOI: 10.1159/000233974
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Cyclosporine-Induced Suppressor Cells in Murine Delayed-Type Hypersensitivity Responses

Abstract: The effect of Cyclosporine A (CsA) on T cell-mediated delayed-type hypersensitivity (DTH) reactions to murine alloantigens was analysed by transferring spleen cells from sensitised and suppressed mice into irradiated naive recipients. Selective removal of Thy1+, Ly1+ or Ly2+ cells prior to intravenous transfer of cells from alloantigen-sensitised mice showed that Ly1+ Thy1+ cells transferred sensitivity. Concomitant treatment of mice with alloantigen and CsA suppressed the DTH response to alloantigens, and spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
(27 reference statements)
2
3
0
Order By: Relevance
“…This UV dose was selected in order to minimize the inflammatory effects of UV irradiation. The finding of prolongation of heart but not of skin allograft survival by UV irradiation ofthe graft recipient is in agreement with our previous studies (11,12) and those of others (13) which have found survivai of primarily vascularized grafts to be more readily prolonged than that of skin grafts in immunosuppressed recipients. This phenomenon is incompletely understood, but factors such as host vascularization of skin grafts in contrast to primarily vascularized cardiac grafts, and site of grafting may trigger different mechanisms of graft rejection.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This UV dose was selected in order to minimize the inflammatory effects of UV irradiation. The finding of prolongation of heart but not of skin allograft survival by UV irradiation ofthe graft recipient is in agreement with our previous studies (11,12) and those of others (13) which have found survivai of primarily vascularized grafts to be more readily prolonged than that of skin grafts in immunosuppressed recipients. This phenomenon is incompletely understood, but factors such as host vascularization of skin grafts in contrast to primarily vascularized cardiac grafts, and site of grafting may trigger different mechanisms of graft rejection.…”
Section: Discussionsupporting
confidence: 93%
“…In other experiments, using footpad swelling measurements, DTH to C3H/He cells was not suppressed by UV-induced C57/B16-specific suppressor cells (data not shown). These data were comparable with previously published findings of antigen-specific suppressor T cells in cyclosporine-treated animals (11). Suppressive activity was removed by cytotoxic treatment of the cells before transfer with anti-Thyl-2 or anti-Lyt2 monoclonal antibodies (group 8 vs group 6, groups 17 or 18 vs group 15), but was not removed by anti-L3T4 or anti-Lyt 1 monoclonal treatment (group 9 vs group 6, group 19 vs group 15).…”
Section: Characterization Of Uv Radiation-induced Suppressors Of Dth supporting
confidence: 93%
See 3 more Smart Citations